Analysis of Failure Mechanics and Energy Evolution of Sandstone Under Uniaxial Loading Based on DIC Technology - Wei, Like; Yuan, Qiang; Ren, Yiwei; Jiang, Deyi; Zhang, Dingding; Liu, Yongliang; Zou, Yunlong; Ren, Shicong (Frontiers in Earth Science, 2022)
The research on the energy evolution process of rock deformation is conductive to essentially reveal the rock failure mechanism, and is of great significance to uncover the breeding of dynamic disasters in rock engineering. In order to characterize the damage evolution of energy dissipation during rock failure, the digital image correlation (DIC) technique is proposed to describe the rock failure mechanics and its energy evolution process. The uniaxial compression experiment of sandstone specimen was carried out, and the whole field deformation and failure characteristics of rock had been captured by the DIC system. The DIC measurement accuracy was verified by the FBG sensor, the elastic region of the specimen was divided according to the location of strain localization zone, and the evolution process of elastic strain energy of rock was analyzed. The results show that the time history development of rock strain obtained by the FBG and DIC system matches identically, and the deviation of peak axial strain of both means is less than 5%, which verifies the applicability of DIC system. The uncoordinated evolution of rock deformation displacement field is discussed to reveal the crack development and failure form of the sandstone specimen under uniaxial compression. The energy evolution of the elastic region of the specimen is revealed, and the development of releasable elastic strain energy would be divided into three stages, which are corresponding to the stress-strain characteristics of rock failure mechanics. This study could provide alternative analytical method for the experiment of rock mechanics and has positive significance.